Land prices and unemployment - Zheng Liu; Jianjun Miao; Tao Zha (Federal Reserve Bank of Atlanta, 2013)
We integrate the housing market and the labor market in a dynamic general equilibrium model with credit and search frictions. The model is confronted with the U.S. macroeconomic time series. Our estimated model can account for two prominent facts observed in the data. First, the land price and the unemployment rate tend to move in opposite directions over the business cycle. Second, a shock that moves the land price is capable of generating large volatility in unemployment. Our estimation indicates that a 10 percent drop in the land price leads to a 0.34 percentage point increase in the unemployment rate (relative to its steady state).
Keywords: E21; E27; E32; E44; 330; Housing and labor markets; volatility; match value of employment; marginal utility of consumption; credit channel; labor channel; Bodenpreis; Immobilienpreis; Schock; Arbeitslosigkeit; Konjunktur; Dynamisches Gleichgewicht; Theorie; Schätzung; USA